Assessment of the Effectiveness of Centella asiatica Ethanol Extract in Alleviating Diarrhea in Castor Oil-Induced White Mice: A Pharmacological Approach - Yuneka Sarisitiana; Fendy Prasetyawan; Faisal Akhmal Muslikh; Ratna Mildawati; Chandra Arifin; Abd Rofiq; Ivan Junius Mesak (Journal Health of Indonesian, 2023)
This study investigated the potential anti-diarrheal effects of ethanol extract from Centella asiatica leaves using a castor oil-induced diarrhea model in mice. The extract, obtained from Centella asiatica leaves, was administered orally to mice at various doses. Parameters including the frequency, duration, and onset of diarrhea were measured and compared with control groups. Results indicated a dose-dependent reduction in diarrhea frequency and duration in treated mice. Higher doses of Centella asiatica ethanol leaf extract demonstrated efficacy comparable to loperamide, a standard anti-diarrheal drug. Histopathological analysis further revealed protective effects on intestinal tissue integrity, suggesting a potential mechanism of action for the observed anti-diarrheal activity. These findings underscore the potential of Centella asiatica ethanol leaf extract as a natural alternative for managing diarrhea. The study contributes to the growing body of evidence supporting the traditional use of Centella asiatica in folk medicine for gastrointestinal ailments. However, further research is warranted to elucidate the underlying mechanisms of action responsible for its anti-diarrheal effects and to conduct clinical trials for human validation. In conclusion, this research highlights the significance of exploring natural remedies derived from medicinal plants like Centella asiatica for combating gastrointestinal disorders. The study underscores the potential of Centella asiatica ethanol leaf extract as a therapeutic agent for managing diarrhea and improving public health outcomes.